2022
DOI: 10.1002/pssa.202100618
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Nanotubes and Breakdown Voltage in GaN p–i–n Diodes

Abstract: The failure analysis of a GaN p–i–n diode is carried out by current–voltage (I–V) tests, emission microscope (EMMI), focused ion beam (FIB), and scanning electron microscope (SEM). A nanotube is found at the location of the luminous spot in the EMMI test. Intentional breakdown experiments show that the breakdown voltages of about 1/3 diodes with the size of are lower than 50 V. These proportions are 1/2 and 5/6 for the diodes with the size of and respectively. At the breakdown injuries of some diodes, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Therefore, it is inferred that points 1, 2, 4, and 5 are likely to undergo breakdown, resulting in a sharp increase in leakage current, while the electrical properties of dot 3 may not have changed significantly. In our previous work, it was found that breakdown can form new leakage channels, and the breakdown of the devices is related to the nanopipes in the material, and the specific information can be found in the literature [20]. In this paper, we are more interested in the structural defects of the leakage triggered in the diodes, and therefore further analysis of dot 3 was performed.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Therefore, it is inferred that points 1, 2, 4, and 5 are likely to undergo breakdown, resulting in a sharp increase in leakage current, while the electrical properties of dot 3 may not have changed significantly. In our previous work, it was found that breakdown can form new leakage channels, and the breakdown of the devices is related to the nanopipes in the material, and the specific information can be found in the literature [20]. In this paper, we are more interested in the structural defects of the leakage triggered in the diodes, and therefore further analysis of dot 3 was performed.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Gallium nitride (GaN) has the properties of a wide bandgap, high thermal conductivity, high breakdown voltage, high electron saturation velocity, high electron mobility, and strong radiation resistance, which makes it particularly suitable for applications requiring high temperatures and harsh environments. [1,2] Because of these advantages, GaN-based detectors have been extensively studied and one specific area of focus in GaN-based research is the development of ultraviolet (UV) detectors. UV detectors have a wide range of military and civil applications, such as missile warning, flame detection, medical imaging, sterilization, purification, and so on.…”
Section: Introductionmentioning
confidence: 99%